2015
DOI: 10.1158/1541-7786.mcr-14-0384-t
|View full text |Cite
|
Sign up to set email alerts
|

RSK Promotes Prostate Cancer Progression in Bone through ING3, CKAP2, and PTK6-Mediated Cell Survival

Abstract: Prostate cancer (PCa) has a proclivity to metastasize to bone. The mechanism by which PCa cells are able to survive and progress in the bone microenvironment is not clear. Identification of molecules that play critical roles in the progression of PCa in bone will provide essential targets for therapy. Ribosomal S6 protein kinase (RSKs) have been shown to mediate many cellular functions critical for cancer progression. Whether RSK plays a role in the progression of PCa in bone is unknown. Immunohistochemical (I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…We also observed that the fraction of proteins overlapping with any of the “hallmark” gene sets to be higher when including the phosphoproteomic data, accounting for any potential study bias. These results provide evidence of actionable phosphorylation events in metastatic CRPC, several of which have previously been implicated in this disease including PRKDC, PRKAA2, and AKT (Goodwin et al, 2015; Yu et al, 2015) (Park et al, 2009) while others such as RPS6KA4 and MCM2 represent new drug targets.…”
Section: Resultsmentioning
confidence: 58%
“…We also observed that the fraction of proteins overlapping with any of the “hallmark” gene sets to be higher when including the phosphoproteomic data, accounting for any potential study bias. These results provide evidence of actionable phosphorylation events in metastatic CRPC, several of which have previously been implicated in this disease including PRKDC, PRKAA2, and AKT (Goodwin et al, 2015; Yu et al, 2015) (Park et al, 2009) while others such as RPS6KA4 and MCM2 represent new drug targets.…”
Section: Resultsmentioning
confidence: 58%
“…RSKs function downstream of MEK, ERK and protein kinase C, and are frequently activated in various types of cancer, including leukemia, and this activation may be triggered by steroids, insulin, epidermal growth factor and estrogen. Previous studies have demonstrated that RSK1 is overexpressed in prostate (28), breast (29) and colon cancer tissues (30).…”
Section: A B Discussionmentioning
confidence: 99%
“…The Rsk2 inhibitor SL0101-1 was purchased from Santa Cruz Biotechnology (Santa Cruz, CA). A constitutively active (CA) RSK2 construct (35) was provided by Dr. Sue-Hwa Lin (MD Anderson, Houston, TX). Three human breast cancer cell lines were used in these studies.…”
Section: Methodsmentioning
confidence: 99%